Etika profesi kedokteran dalam perspektif literatur medis islami: Tanggung jawab dan amanah dokter dalam pandangan islam - Sari, Rizky Wulan; Adilya, St. Liftira; Hendriansyach, Yahya Alfian; Amiruddin, Muhammad (Maliki Interdisciplinary Journal, 2026)
The ethics of the medical profession in Islam serves as a moral and spiritual guideline that directs physicians to act based on Islamic values. This ethical framework emphasizes not only professional responsibility toward patients but also sincerity, trustworthiness (amanah), and compassion in providing healthcare services. Core principles such as the protection of life (hifz an-nafs), honesty, justice, and patient confidentiality form the foundation of Islamic medical practice. Beyond its function as an individual moral guide, Islamic medical ethics also carries a broad social dimension. Physicians are regarded as individuals who bear great responsibility for the welfare of society. Thus, a doctor’s role extends beyond healing diseases to include protecting life and promoting humanitarian values. These values distinguish Islamic medical ethics from conventional medical ethics, which often focus primarily on professional competence rather than spiritual accountability. Applying Islamic medical ethics in the modern era presents challenges amid technological advances and the globalization of values. Integrating modern medical science with Islamic ethical principles is essential to ensure that healthcare remains oriented toward the benefit (maslahah) of humanity. By understanding and practicing Islamic medical ethics comprehensively, medical professionals can provide services that are not only professional and empathetic but also spiritually meaningful, achieving harmony between medical, moral, and spiritual dimensions in healthcare practice.